The Influence of Work Engagement and Ambidextrous Organization on Employee Performance with Innovative Behavior as a Mediating Variable at the Housing and Settlement Area Agency of North Sumatra Province - Saputra, Ade; Siahaan, Elisabet; Sembiring, Beby Karina Fawzeea (Indonesian Journal Publisher, 2025)
In a dynamic work environment, employee performance is influenced by the level of work engagement and the organization’s ability to manage exploration and exploitation in a balanced manner (ambidexterity). Organizations that effectively implement ambidexterity can encourage employees to be more innovative, ultimately contributing to improved performance. This study aims to examine and analyze the influence of work engagement and organizational ambidexterity on employee performance, with innovative behavior as a mediating variable at Dinas Perumahan dan Kawasan Permukiman Provinsi Sumatera Utara. This is a quantitative study using an explanatory research design. The population in this study consists of all employees at Dinas Perumahan dan Kawasan Permukiman Provinsi Sumatera Utara, totaling 75 individuals. The sampling method used was a saturated sample, in which the entire population was used as the research sample. Data were analyzed using Structural Equation Modeling. The results show that work engagement has a direct, positive, and significant effect on employee performance, and organizational ambidexterity also has a direct, positive, and significant effect on employee performance. Furthermore, innovative behavior has a direct, positive, and significant effect on employee performance, and both work engagement and organizational ambidexterity have a direct, positive, and significant effect on innovative behavior. Indirectly, work engagement and organizational ambidexterity positively and significantly influence employee performance at Dinas Perumahan dan Kawasan Permukiman Provinsi Sumatera Utara through the mediation of innovative behavior